Integration of Digital Storytelling in Project-Based Learning to Develop Students Historical Literacy: Literature Review - Setyo Purwoto; Ganda Febri Kurniawan (STKIP Taman Siswa Bima, 2025)
In the digital era, history learning in schools faces the challenge of low student historical literacy which is reflected in the weak understanding of chronology, historical concepts and source analysis skills. This research aims to analyse the integration of digital storytelling into the Project-Based Learning (PjBL) model as a strategy to strengthen students' historical literacy. Using the Systematic Literature Review approach, 15 primary articles from various journals and proceedings were systematically reviewed. The results of the study revealed that the application of digital storytelling in PjBL effectively improved the five indicators of historical literacy namely historical knowledge, conceptual understanding, source analysis skills, historical awareness and the use of historical language with more active student participation and more contextual narratives. Constraints such as limited infrastructure, teacher competence and access to credible sources are still the main obstacles. Therefore, intensive training for teachers, strengthening digital infrastructure and adaptive curriculum integration are needed to ensure the effectiveness of technology-based history learning models in Indonesia and support the implementation of Merdeka Curriculum.